ANALISIS KUALITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENUMBUHKAN NILAI-NILAI MODERASI BERAGAMA DI SMA NEGERI 15 MEDAN - Nugraha, Muhammad Akbar; Muchtar, Asmaji; Makhsun, Toha (Jurnal Ilmiah Penelitian Mahasiswa, 2025)
This research aims to analyze the implementation of Islamic education learning methods, the role of Islamic Education teachers, and the factors affecting the quality of learning in instilling the values of religious moderation at SMA Negeri 15 Medan. The research approach uses a qualitative descriptive method with data collection through interviews, observations, and document studies. The research results show that the Islamic religious education methods applied include dialogue approaches, case studies, project-based learning, the use of multicultural resources, contextual learning, and collaborative learning. These methods are effective in enhancing students' understanding of moderate, tolerant, and applicable religious values. The role of Islamic Religion teachers is very significant as facilitators and role models in fostering attitudes of tolerance, justice, and cooperation among students. The competence of teachers, leadership, and the ability to understand students' backgrounds are key to the success of implementing religious moderation. Factors that influence the quality of learning consist of internal and external aspects. Internal factors include teacher competence, student motivation, and teaching methods, while external factors encompass school policy support, availability of facilities, and an inclusive social environment. The synergy between teachers, students, school staff, and parents becomes an important foundation in the successful implementation of religious moderation values. This research concludes that the application of religious moderation values not only enhances the quality of Islamic religious education but also shapes students who are capable of living harmoniously in a diverse society.Keywords: Religious moderation, teaching methods, teacher's role, quality of learning, Islamic religious education.